Efficacy of Azadirachta indica and Zingiber officinale on Hirsutism in Polycystic Ovarian Disease: A Randomized Controlled Trial - Anjum, Dr. Farzana; Shameem, Dr. Ismath; Mubeen, Prof. Umraz (International Journal of Innovative Research in Medical Science, 2018)
Background & objectives: Hirsutism is defined as excessive terminal hair growth on androgen dependent areas of the body in women, which grows in a typical male distribution pattern. Polycystic ovarian disease (PCOD) is the most common cause of it, in 70-80% of women. Hirsutism is recognized to cause profound distress in affected women. Despite of available conventional treatment modalities, its management is still a challenge for physicians. The present study was conducted to evaluate the efficacy and safety of bark of Azadirachta indica (poste darakht Neem) and Zingiber officinale (Zanjabeel) on hirsutism in polycystic ovarian disease. Methods: A randomized controlled clinical study was carried out at Institute’s Hospital, Bengaluru. 40 hirsute women with Modified ferriman gallwey score (mFGS) of >6 associated with polycystic ovarian syndrome were assigned to two groups. In test group, decoction of Neem 24 g and Zanjabeel 4 g was given in 2 divided doses and in control group, standard drug (tablet cyproterone acetate 2 mg & ethinyl estradial 0.035 mg) was administered orally from 5th day of cycle for 21 days/cycle for three consecutive cycles for 3 months. Menstrual cycle pattern, ferriman gallway score, body mass index, hormonal assay, lipid profile, pelvic ultrasonography and safety profile were assessed during the trial. Data was analysed with student t test, chi square test and fisher exact test. Results: Fasting insulin (p=0.030), lipid profile (p<0.001) were reduces significantly in test as compared to control group. Modified ferriman gallwey score (p=0.950), body mass index (p=0.235), free testosterone ((p=0.185), and luteinizing hormone (p=0.203), reduced in test group similar to control group. Significant improvement of menstrual cycle was reported in control group (p=0.039) after treatment. Follicle stimulating hormone remained unchanged in both groups. Interpretation and conclusion: The test drugs poste darakht Neem and Zanjabeel are as effective as control group to improve Modified ferriman-gallwey score, bio chemical and hormonal changes in hirsutism due to PCOD.